Healthcare System Priorities for Successful Integration of Genomics: An Australian Focus - Belinda L. Burns; Gemma A. Bilkey; Gemma A. Bilkey; Emily P. Coles; Faye L. Bowman; John P. Beilby; John P. Beilby; Nicholas S. Pachter; Nicholas S. Pachter; Gareth Baynam; Gareth Baynam; Gareth Baynam; et al. (Frontiers Media S.A., 2019)
This paper examines key considerations for the successful integration of genomic technologies into healthcare systems. All healthcare systems strive to introduce new technologies that are effective and affordable, but genomics offers particular challenges, given the rapid evolution of the technology. In this context we frame internationally relevant discussion points relating to effective and sustainable implementation of genomic testing within the strategic priority areas of the recently endorsed Australian National Health Genomics Policy Framework. The priority areas are services, data, workforce, finances, and person-centred care. In addition, we outline recommendations from a government perspective through the lens of the Australian health system, and argue that resources should be allocated not to just genomic testing alone, but across the five strategic priority areas for full effectiveness.